The evolutionary ecology of aquatic insect range limits: a mechanistic approach using thermal tolerance - Shah, Alisha Ajay, author; Ghalambor, Cameron K., advisor; Funk, W. Chris, advisor; Poff, N. LeRoy, committee member; Clements, William H., committee member (Colorado State University. Libraries, 2018)
Understanding the effect of climate variability on species physiology and distribution is a longstanding and largely unresolved challenged in evolutionary ecology with important implications for vulnerability to climate change. My dissertation is focused on understanding the effects of temperature on physiological traits and genetic population structure of aquatic insects, to better understand the mechanisms that underlie their elevation range distributions. For my first chapter, I tested the hypothesis proposed by Dan Janzen in 1967, that temperate mountain species should have broad thermal tolerances thus allowing them to disperse easily across elevation, unhindered by the novel temperatures they encounter. On the other hand, tropical species should exhibit narrower thermal tolerances in response to the stable climate they experience. They should be physiologically challenged to disperse and be restricted to a narrow elevation range distribution. I measured critical thermal limits (CTMAX and CTMIN) and thermal breadth (difference between CTMAX and CTMIN) in several phylogenetically related temperate (Colorado) and tropical (Ecuador) aquatic insect species. I found that, as predicted, species that encounter wider stream temperature ranges, such as temperate species and high elevation tropical species, have broader thermal breadths compared to their tropical and low elevation relatives. Next, I tested how plastic the critical thermal maximum (CTMAX) response was in a subset of aquatic insects. Greater acclimation ability is thought to allow species to withstand the large temperature fluctuations associated with different seasons. Implicit in Janzen's hypothesis, is the assumption that temperate species have greater acclimation ability compared to tropical species. My experiments revealed that temperate and high elevation tropical mayfly species had greater acclimation ability compared to their relatives. However, we found no differences in acclimation capacity in stoneflies. Temperature may therefore not affect all species equally, and species acclimation ability may be a result of other factors such as body shape and evolutionary history. I then measured a third trait, metabolic rate, to investigate how it varies with temperature in temperate and tropical mayflies. Metabolic rate is arguably one of the most important traits for species because it determines the amount of energy an animal has available for its activities. I found that metabolic rates vary between temperate and tropical mayflies, and that temperatures away from a certain optimum are stressful and sometimes lethal for tropical but not temperate mayflies. Finally, I linked thermal tolerance to dispersal by correlating gene flow among populations with pairwise differences in the physiological trait CTMAX. Analyses revealed that there was lower gene flow (higher FST) among populations in Ecuador than among populations in Colorado. Within Ecuador, differences in CTMAX were highly correlated with maximum stream temperature, which was found to best explain tropical mayfly genetic structure. In Colorado, no environmental or physiological variable was found to explain population structure. Our results indicate, as Janzen predicted, that temperature can act as a significant barrier to dispersal among tropical populations but not in temperate ones. Thermal sensitivity measured as CTMAX was also correlated with FST but was not significant. As a whole, the results from my research lend support to Janzen's hypothesis and suggest that temperature plays an important role in determining range limits of aquatic insect species through its effect of thermal tolerance traits. While this research addresses long standing questions in ecology and evolution, it also has conservation implications. Most importantly, as the effects of global climate change augment, the thermally sensitive tropical species from this study system are at particular risk for extreme population declines or even extinction.
Keywords: biodiversity; sensitivity to climate change; tropical; range limits; aquatic insects; thermal tolerance